Flux weakening control of electric starter-generator based on permanent-magnet machine - Bozhko, Serhiy; Rashed, Mohamed; Hill, Chris; Yeoh, Seang Shen; Yang, Tao (Institute of Electrical and Electronics Engineers, 2017)
The paper presents control analysis and design for a Permanent Magnet Machine (PMM) operated in Flux-Weakening (FW) mode for an aircraft electric starter-generator application. Previous literature has focused on FW control of PMMs in motoring (starting) mode, however the system stability and control in generating mode has been inadequately studied. The paper reports detailed, rigorous control analysis and design for a PMM based aircraft electric starter-generator operated in flux-weakening mode. It is shown that an unstable area of operation exists. A novel control scheme which eliminates this instability is proposed. The key analytical findings of the paper are verified by experimental investigation. The paper therefore concludes that the presented technique is able to ensure system stability under all modes of operation. Furthermore, it is noted that the findings of this work are also valuable for any two-quadrant PMM drive with frequent change between starting and generating regimes under current-limiting operation.